Annotazioni su un componimento a una poesia di Pere Miquel Carbonell. - Letizia, Michela (Scripta, 2022)
have selected from the anthology La poesia oggettiva nella letteratura catalana medievale (Objective Poetry in Medieval Catalan Literature) by A. M. Compagna, M. Letizia and N. Puigdevall Bafaluy (Roma, Aracne 2019), the text by Pere Miquel Carbonell, «Vos, en Galant, vergonya teniu poca» (pp. 177-180): I aim to shed further light on its content, its rhetorical instrumentation, and the author’s modes of expression.